2017
DOI: 10.1016/j.rbmo.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin resistance in men with unexplained infertility

Abstract: This prospective case-control study aimed to test the presence of insulin resistance (IR) in men with unexplained infertility. We included two groups: the study group including 160 infertile men with unexplained oligozoospermia (sperm count <10 × 10/ml) and normal hormonal profile, and the control group of 79 men with proven fertility within the preceding year. A fasting blood test measured IR, FSH, LH, total cholesterol, low-density lipoprotein, high-density lipoprotein and triglycerides. Insulin level was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our findings agreed also with Mansour et al. (2017); who stated that insulin resistance was found to be higher in patients with unexplained infertility in comparison with controls.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings agreed also with Mansour et al. (2017); who stated that insulin resistance was found to be higher in patients with unexplained infertility in comparison with controls.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that diabetes is accompanied by augmented levels of apoptosis of germ cells in testes and disturbance of spermatogenesis [27,28], which are associated with hormonal alterations, oxidative stress and hyperglycemia [29]. Diabetic subjects have reduced anti-oxidant capacity and/or raised oxidative damage in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Dill also ameliorated HOMA-IR in T2D rats. Notably, insulin resistance is of extreme importance in spermatogenesis since insulin controls the metabolic co-operation between testis and its need for normal testicular action [29].…”
Section: Discussionmentioning
confidence: 99%
“…Vitiated Medo Dhatavagni will also lead to the productions of Aama, which circulates in the whole body, affecting the metabolism as well as nourishment of other Dhatu. These factors produce a circumstance of over nourishment of Meda Dhatu and undernourishment of other Dhatu (Shrikanth et al, 2009;Dwivedi et al, 2016e) The whole mechanism can be understood from the different manifestation of obesity as described in Figure 1 ( Nagpal et al, 2018;Oussaada et al, 2019;Simonds et al, 2012;Romeo et al, 2012;Akhmedov and Berdeaux, 2013;Patel et al, 2018;Cao, 2011;Jungheim et al, 2012;Mansour et al, 2017;Crujeiras and Casanueva, 2015).…”
mentioning
confidence: 99%